Uncovering Carpal Tunnel Syndrome Risk through Genetics: A Path to Early Prevention - Fair, Jacques; Shi, Caitlin; Amin, Harshit; Gunawardena, Tharidu; Abernathy, Sarah; Kottapalli, Sai; Thompson, Sophia; Amabile, Thomas; Shah, Kush; Caughey, Curtis; Anand, Kirin; Sahu, Abhinav; et al. (International Journal of Innovative Research in Medical Science, 2023)
Carpal Tunnel Syndrome (CTS) is a common disorder that affects the hand, caused by compression of the median nerve at the wrist. Despite its prevalence and impact on individuals, the underlying biological mechanisms of CTS remain poorly understood. Moreover, there is a lack of strategies for identifying individuals at risk for CTS in order to prevent its development. In recent years, the use of genome sequencing, genetic analysis, and genome-wide association studies (GWAS) has revealed several genetic factors that may be associated with CTS, including specific genes and gene loci. A Genetic Risk Score (GRS) that incorporates these findings could potentially be used to predict the likelihood of developing CTS and enable earlier identification and prevention of the condition. GWAS has already demonstrated a correlation between CTS severity and a GRS composed of 13 susceptibility loci. Further research on the development of a more comprehensive GRS for CTS could potentially reduce the overall burden of this disorder.